Schooling for Sustainable Development in Europe : Concepts, Policies and Educational Experiences at the End of the UN Decade of Education for Sustainable Development - Jucker, Rolf; Mathar, Reiner (Schooling for Sustainable Development ;, 2015)
This book examines the implementation of Education for Sustainable Development (ESD) programs in schools across Europe. It describes and analyzes how individual countries and the region as a whole have established teaching and learning methods to help students develop the competencies needed to be part of a sustainable society. Featuring chapters written by experts throughout Europe, the book first provides a general overview of ESD in various contexts, including the state-of-the-art of ESD theory and conceptual development; political and social analysis; the various concepts of ESD competencies; and teacher training. Next, the book details how ESD has been implemented in different European countries and regions, including: Sweden, Italy, Germany, Austria, Switzerland, Catalonia, Hungary, Finland, Norway, Denmark, Flanders, France, Cyprus, UK, and the Netherlands. In recognition of education as a motor of change, the United Nations General Assembly declared a Decade of Education for Sustainable Development (2005-2014), calling for the integration of sustainable development into all aspects of education and learning. Inside this book, readers will find details on what has been done, as well as assessments of what more could be done, across Europe. It will help readers gain valuable insights into how to help students develop the knowledge, skills, and values needed to shape a sustainable future.